Analisis Keterampilan Passing Bawah Bola Voli Putri Berdasarkan Siklus Menstruasi di Klub Voli Tunas Muda Muara Bulian - Desinta Kurniasari; Anggel Hardi Yanto; Bangkit Yudho Prabowo; Iwan Budi Setiawan; Alek Oktadinata (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze women's volleyball passing skills based on the menstrual cycle at the Tunas Muda Muara Bulan volleyball club. This study used a quantitative approach with a One Group Pretest-Posttest Design on 17 female volleyball athletes selected through total sampling. Data were obtained through a test of underhand passing skills before (pretest) and during menstruation (posttest). The results showed an average pretest score of 40.529 (very good category) and a posttest score of 24.117 (good-very good category). The Paired Sample T-Test produced a significance value of 0.000 (<0.05), which means there is a significant difference between the results before and during menstruation. The N-Gain Score value of -0.3094 indicates a decrease in skills in the moderate category. It was concluded that the menstrual cycle affects the underhand passing skills of female volleyball athletes, so coaches need to adjust the training intensity and pay special attention to the condition of athletes during the menstrual period. Keywords: Menstruation, Underhand Pass, Volleyball, Female Athletes, Performance